Covered California kickoff and information fair Oct.1 - Uribes, Tom::::::::: (2013)
With the Affordable Care Act taking effect in 2014 and the enrollment period beginning Oct. 1, Fresno State will participate in two projects to educate Californians about the new state health insurance exchange, Covered California™.